Placebo influences on dyskinesia in Parkinson's disease - Goetz, Christopher G.; Laska, Eugene; Hicking, Christine; Damier, Philippe; Müller, Thomas; Nutt, John; Warren Olanow, C.; Rascol, Olivier; Russ, Hermann (Movement disorders, 2008)
Clinical features that are prognostic indicators of placebo response among dyskinetic Parkinson's disease patients were determined. Placebo‐associated improvements occur in Parkinsonism, but responses in dyskinesia have not been studied. Placebo data from two multicenter studies with identical design comparing sarizotan to placebo for treating dyskinesia were accessed. Sarizotan (2 mg/day) failed to improve dyskinesia compared with placebo, but both treatments improved dyskinesia compared with baseline. Stepwise regression identified baseline characteristics that influenced dyskinesia response to placebo, and these factors were entered into a logistic regression model to quantify their influence on placebo‐related dyskinesia improvements and worsening. Because placebo‐associated improvements in Parkinsonism have been attributed to heightened dopaminergic activity, we also examined the association between changes in Parkinsonism and dyskinesia. Four hundred eighty‐four subjects received placebo treatment; 178 met criteria for placebo‐associated dyskinesia improvement and 37 for dyskinesia worsening. Older age, lower baseline Parkinsonism score, and lower total daily levodopa doses were associated with placebo‐associated improvement, whereas lower baseline dyskinesia score was associated with placebo‐associated worsening. Placebo‐associated dyskinesia changes were not correlated with Parkinsonism changes, and all effects in the sarizotan group were statistically explained by the placebo‐effect regression model. Dyskinesias are affected by placebo treatment. The absence of correlation between placebo‐induced changes in dyskinesia and Parkinsonism argues against a dopaminergic activation mechanism to explain placebo‐associated improvements in dyskinesia. The magnitude and variance of placebo‐related changes and the factors that influence them can be helpful in the design of future clinical trials of antidyskinetic agents. © 2007 Movement Disorder Society